Detection of anti-Toxoplasma gondii antibodies in wild animals from two zoological parks in Algiers, Algeria. - Cherif, AM; Benfodil, K; Khouchene , N; Ansel, S; Ait-Oudhia, KH (Journal of the Hellenic Veterinary Medical Society, 2024)
Toxoplasmosis is the most frequent parasitic diseases in the world. Caused by the protozoan Toxoplasma gondii, itcouldaffect most warm-blooded animals howeveronly felids are its definitive hosts. Eighty-sixblood samples were collected from different animal species raised in captivity withintwo Zoological Parksofthe Algiers urban area. Sera from eighteen birds and sixty eighty mammals were assayed for the presence of T. gondii antibodies by the ELISA test. The overall prevalence of Toxoplasma gondii infection was 58.1%. By ELISA, T. gondii antibodies were found in 38.9% of birds, in 75% of primates, in 75% of carnivores and in 56.8% of herbivores. All seropositive animals were apparently healthy. This contribution represents the first report ofT.gondiiseroprevalence in captive wild animals from Algiers zoological Parks. The obtained results indicate a widespread exposure of Algerianzoo animals in to T. gondii.